2013
DOI: 10.5539/gjhs.v5n5p41
|View full text |Cite
|
Sign up to set email alerts
|

“There is no other option; we have to feed our families…who else would do it?”: The Financial Lives of Women Engaging in Sex Work in Ulaanbaatar, Mongolia

Abstract: Introduction:This article provides an overview of the financial lives of women (n = 204) engaging in sex work in Ulaanbaatar, Mongolia.Methods:This paper presents findings from a computer-based, interviewer-administered baseline assessment administered with women recruited for participation in a randomized controlled trial testing the feasibility of a combined HIV risk reduction and savings-led microfinance intervention for women engaging in sex work in Mongolia.Findings:Findings demonstrate that most women ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
(33 reference statements)
1
23
0
Order By: Relevance
“…As both primary caregivers and the primary income source for their families, 40 women reported missing sessions because of family emergencies, their poor health or that of their children or parents, or alcohol use. Such daily challenges may not be surmountable, but methods to consolidate the intervention to fewer sessions or to offer weekend workshop formats or use of technology such as mobile phones to deliver session content could be tested as more manageable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…As both primary caregivers and the primary income source for their families, 40 women reported missing sessions because of family emergencies, their poor health or that of their children or parents, or alcohol use. Such daily challenges may not be surmountable, but methods to consolidate the intervention to fewer sessions or to offer weekend workshop formats or use of technology such as mobile phones to deliver session content could be tested as more manageable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of "upstream" drivers of HIV (Auerbach, Parkhurst, & Caceres, 2011;Gupta, Ogden, & Warner, 2011), there have been calls to address structural issues and economic factors that impede or facilitate HIV risk-reduction (Blankenship, Friedman, Dworkin, & Mantell, 2006; Joint United Nations Programme on HIV/ AIDS, 2012; Sumartojo, 2000;Sumartojo, Doll, Holtgrave, Gayle, & Merson, 2000;WHO, 2005), but there is surprisingly little information on the financial needs and habits of FSWs, aside from two examples from Asia (Ngo et al, 2007;Tsai et al, 2013). Integrated economic strengthening approaches to HIV prevention for FSWs have proceeded nonetheless, to mixed results.…”
Section: Efforts To Address Structural Drivers Of Hiv Transmissionmentioning
confidence: 99%
“…However, contextual, social, and structural factors such as stigma, criminalization, discriminatory policies, gender-based violence, and poverty further exacerbate sex workers' vulnerability to HIV (Baral et al, 2012;Papworth et al, 2013;WHO, 2015) by reducing opportunities for or disincentivizing HIV risk-reduction practices. For example, underlying economic determinants of HIV risk affect women's decisions about whether and how they will take part in sex work (Baleta, 2015;Bamba et al, 2014;Karamouzian et al, 2016;Kiernan, Mishori, & Masoda, 2016;Scorgie et al, 2012;Strathdee, Crago, Butler, Bekker, & Beyrer, 2015), and many economic strengthening programs for FSWs are premised on observations that economic vulnerability and food insecurity can lead to riskier sexual transactions, including condomless and anal sex (Beckham, Shembilu, Winch, Beyrer, & Kerrigan, 2015;Cange et al, 2017;Elmes et al, 2014;Scorgie et al, 2012;Tsai et al, 2013;Tucker, Krishna, Prabhakar, Panyam, & Anand, 2012;Veldhuijzen et al, 2011;Weiser et al, 2007). Rather than attempting to directly change proximal-level sexual risk behaviors, these economic strengthening-focused HIV prevention programs attempt to change distal economic factors, by stabilizing income and/or increasing economic resilience, as a means of empowering women to reduce financially-driven decisions about sex partners or practices (Ndoye, 2010;Odek et al, 2009) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown associations between sexual risk behavior with clients and lower education (Fernandes et al, 2014), older age (Hao et al, 2014), being married (Kamal, Hassan, & Salikon, 2013), and having dependent children (Reed et al, 2013; Tsai et al, 2013; Witte, Batsukh, & Chang, 2010). Substance use has also been associated with increased vulnerability among FSWs to HIV/STIs (Medhi et al, 2013; Strathdee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%